The super-classical-Boussinesq hierarchy and its super-Hamiltonian structure - 陶司兴 夏铁成 (Chinese physics B, 2010)
Based on the constructed Lie superalgebra, the super-classical-Boussinesq hierarchy is obtained. Then, its super- Hamiltonian structure is obtained by making use of super=trace identity. Furthermore, the super-classical-Boussinesq hierarchy is also integrable in the sense of Liouville.